Microplastic Levels in Water and Sediment of Karaçomak Dam Lake (Kastamonu, Türkiye) - Taştan, Yiğit; Sönmez, Adem Yavuz (Journal of Agricultural Production, 2024)
This paper investigates the microplastic (MP) abundance and morphology in Karaçomak Dam Lake, a freshwater source used for irrigation and drinking water, located in Kastamonu, Türkiye. Water and sediment samples were collected during January, April, July and October 2023 from two stations determined on the lake. MPs obtained from the samples were counted and classified according to their sizes, shapes (fiber, fragment, film, microbead) and colors. Results showed that the mean MP abundance in the water samples was 3206 particle/m3, while it was 180 particle/kg dry weight in the sediment samples. The most frequent MP type was fiber in surface water samples and fragment in sediment samples. Predominant colors were blue and black for surface water and sediment, respectively. Majority of the MPs found were small-sized MPs (<1 mm). MP abundance was the highest in winter season, followed by autumn, spring and summer, respectively. The seasonal differences were probably driven by rainfall and the anthropogenic activities around the lake. We concluded that the values obtained in this study are moderate in comparison with the literature data. Although it was inferred that sources of MP are domestic waste, agriculture and recreational activities, it is recommended to conduct more comprehensive studies to better understand the sources of MP pollution in Karaçomak Dam Lake.
Keywords: Karaçomak Dam Lake; Plastic; Pollution; Sediment; Water; Sulama Suyu Kalitesi; Water Resources and Water Structures; Su Kaynakları ve Su Yapıları; Irrigation Water Quality